The Role of Iraqi Channel in Reinforcing the Hygienic Awareness - Kadhim Al-Essa, Mohammed R (International Journal of Psychosocial Rehabilitation, 2020)
The present research tackles the hygienic TV Programs that are shown through the Iraqi Satellite Channel as a mass medium that have their characteristics which help them disseminate the health awareness and culture. This also helps in identifying the ranges of observation of these programs and how much the health information has been acquired. Such programs have also the ability to reinforce the awareness concerning health, health awareness, and healthy alimentation and practicing physical exercises. This is done via offering devices and instructions that satisfy the Iraqi Satellite Channel audience. The present research is a regarded as a descriptive one. The researcher has used the survey method and questionnaire for data collecting. The duplication method and percentages have been applied to a sample of (500) of Baghdad people. The research has come to a number of results. Chief among them is that The TV programs introduced by the Iraqi Satellite Channel help the audience acquire the hygienic information that stimulates them to be safe and healthy and stabilizing the health awareness, a matter that later makes them satisfy with these programs. The research dealt with health television programs that are presented through the Iraqi satellite channel as a media that has its advantages and characteristics that make it capable of disseminating culture, awareness and health education, and determining the viewing rates of these programs and the extent of acquiring health information from them and its contribution to stimulating health preservation, planting health awareness and caring for healthy nutrition and practicing Sports through advice and praise that satisfies viewers of the Iraqi satellite channel. This research is considered descriptive research, as the researcher used the survey method and the questionnaire to collect information and conduct the method of repetitions and percentages on a sample of (500) singles representing the audience of the city of Baghdad with its sides Karkh and Rusafa. Iraqi Satellite TV helps viewers gain health information that motivates them to maintain health, establish health awareness, and achieve satisfaction with them (such programs).